Production and tendency in milk processing in Montenegro - Joksimović Miljan; Ivanović Sanjin; Janković-Šoja Svjetlana (Ekonomika Poljoprivrede (1979), 2020)
Production and processing of milk represents a very important sector of the agricultural industry of Montenegro. Milk production is performed primarily on family farms, from which a small percentage is further placed in processing facilities. In addition to favourable conditions for cattle rearing and milk production, production results are modest. ARIMA model was applied in order to forecast the quantities of cow's milk that will be collected and processed in 2019 into fermented dairy products and drinking milk. The observed and obtained data show the presence of seasonal and trend component in time series. Furthermore, the analysis highlighted the importance of milk processing on family farms, in addition to the need for investment in its improvement. The paper also analyzes investment support referring to the milk processing facilities in Montenegro.